Histopathological overview of wound healing process in white rats (Rattus norvegicus) using Chromolaena odorata leaf jelly extract - Indra Yudhika; Muhammad Jailani; Dasrul (Surgical Residency Program Syiah Kuala University, 2021)
Background: Various efforts have been made to accelerate the wound healing process in white rats, one of which is using Chromolaena odorata. The leaves contain tannins, phenols, flavonoids, saponins, and steroids, which accelerate the wound healing process. The purpose of this study was to determine the effect of Chromolaena odorata leaf jelly extract on the wound healing process in the inflammatory and proliferative phases in white rats microscopically (Rattus norvegicus). Methods: A total of 27 healthy adult male white rats aged 3-4 months old were given open wounds on the back measuring 2x2 cm. The rats were then divided into four groups, a group administered with jelly without Chromolaena odorata leaf jelly extract (P0) and groups administered with Chromolaena odorata leaf jelly extract with concentrations of 10% (P1) and 30% (P2), respectively. Chromolaena odorata leaf jelly extracts were given daily by rubbing them on the wound surfaces. Skin biopsies were collected and evaluated histopathologically on days 3, 7, and 14 post-treatment. The histological assessment of wound healing was based on epithelialization and collagen density using Nagaoka criteria. The data were analyzed by analysis of variance (ANOVA) and continued with the Duncan test. Results: The Duncan test results showed that the mean score of the degree of epithelialization and collagen density of wound tissue on days 7 and 14 was significantly higher in the P2 group compared to the P0 and P1 treatments, while the P1 group was not significantly different from P0. Conclusions: In conclusion, the administration of Chromolaena odorata leaf jelly extract could accelerate the degree of epithelialization and collagen density in the wound healing process of the inflammatory and proliferative phases of white rats (Rattus novergicus).